1994
DOI: 10.1038/370270a0
|View full text |Cite
|
Sign up to set email alerts
|

Structure and mechanism of interleukin-lβ converting enzyme

Abstract: Interleukin-1 beta converting enzyme (ICE) processes an inactive precursor to the proinflammatory cytokine, interleukin-1 beta, and may regulate programmed cell death in neuronal cells. The high-resolution structure of human ICE in complex with an inhibitor has been determined by X-ray diffraction. The structure confirms the relationship between human ICE and cell-death proteins in other organisms. The active site spans both the 10 and 20K subunits, which associate to form a tetramer, suggesting a mechanism fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
597
0
11

Year Published

1996
1996
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 817 publications
(631 citation statements)
references
References 37 publications
18
597
0
11
Order By: Relevance
“…In conclusion, we found that IL-6 was has been shown to be a useful strategy for inhibiting induced by IFN-a in vivo, and that this induction was the production of circulating TNF-a 11,12 and IL-1b. 13,14 completely abrogated by the administration of GM. Our In a previous study, we found that gabexate mesilate results indicate that serine protease inhibitors may be (GM), a serine protease inhibitor, suppressed the elevauseful for inhibiting IL-6-relating responses.…”
mentioning
confidence: 93%
“…In conclusion, we found that IL-6 was has been shown to be a useful strategy for inhibiting induced by IFN-a in vivo, and that this induction was the production of circulating TNF-a 11,12 and IL-1b. 13,14 completely abrogated by the administration of GM. Our In a previous study, we found that gabexate mesilate results indicate that serine protease inhibitors may be (GM), a serine protease inhibitor, suppressed the elevauseful for inhibiting IL-6-relating responses.…”
mentioning
confidence: 93%
“…The active enzyme is a tetramer of two p20 subunits surrounding two adjacent p10 subunits, with most of the area of contact between the dimers occurring between the p10 subunits [40,41]. Interactions between the p20 C-terminus and the p10 N-terminus also contribute to the stability of the homodimer.…”
Section: Structure and Functionmentioning
confidence: 99%
“…Crystal structures of caspase-1 (ICE) (Walker et al, 1994;Wilson et al, 1994) and caspase-3 (CPP32/Yama/apopain) (Rotonda et al, 1996) suggest that active forms of caspases are tetramers composed of two pairs of large and small subunits, which are derived from two molecules of a precursor by cleavage at multiple Asp-X bonds. This unusual proteolytic processing suggests that caspase activation is driven by autocatalysis, or by cleavage by other caspases (Martin and Green, 1995).…”
Section: Introductionmentioning
confidence: 99%